The Orthodox Church in Ukraine and Russia after 2013 in the face of political challenges, the Russian-Ukrainian conflict and questions about the limits of sovereignty - Jędraszczyk, Katarzyna (Przegląd Zachodni, Journal of the Institute of Western Affairs in Poznań, Special Issue 2019, s.229-254., 2019)
The aim of the article is to analyse the place and importance of the Orthodox Church in the society and political culture of Ukraine after 2013. The new political realities following the Revolu-tion of Dignity, the annexation of Crimea and the war in Donbas created new challenges for the Or-thodox Church in Ukraine. Particularly important is the influence of the Russian Orthodox Church’s authority over the Ukrainian Orthodox Church of the Moscow Patriarchate.At the turn of 2018 and 2019, by a decision of Patriarch Bartholomew I and with the support of the Ukrainian political authorities, a new reality became fact in Ukrainian Orthodoxy. However, the creation of the Orthodox Church of Ukraine (as a metropolis) does not mean that the split has been overcome. There will be two hostile, equal and comparably strong structures in Ukraine, politically backed by Ukraine and Russia, and this will draw those countries into conflicts over their religious structures and the wealth that their communities possess. At this stage, the Orthodox Church of Ukraine will rely primarily on the potential of the Ukrainian Orthodox Church of the Kiev Patriarchate, and this fact in turn will hinder the transfer of bishops and priests associated with the Moscow Patriarchate. The rift will be difficult to repair.
Keywords: Ukrainian Orthodox Church of the Kiev Patriarchate; Ukrainian Orthodox Church of the Moscow Patriarchate; political culture; Ukraine; national church; tomosof autonomy